2001
DOI: 10.1521/suli.31.3.311.24240
|View full text |Cite
|
Sign up to set email alerts
|

Stressful Life Events and Impulsiveness in Failed Suicide

Abstract: The relationship of recent stressful life events with impulsiveness in triggering suicide attempts and how impulsiveness changes from one suicide attempt to another is unclear. This study used structured-interview tools and standardized measurements to examine the relationship between life stress and impulsiveness in a sample of patients who required hospitalization for a medically serious suicide attempt. After controlling for potentially confounding variables, the number of disrupted interpersonal relationsh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
36
1
4

Year Published

2005
2005
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(46 citation statements)
references
References 22 publications
4
36
1
4
Order By: Relevance
“…The findings also warrant wider implementation of stress management techniques in order to develop adaptive ways to manage stress. The efficacy of these techniques may be enhanced when coupled with strategies to increase personal resilience amongst vulnerable groups (Weyrauch et al, 2001). Finally, while the odd ratios are small, this may be symptomatic of the examination of an "at risk" population.…”
Section: Discussionmentioning
confidence: 99%
“…The findings also warrant wider implementation of stress management techniques in order to develop adaptive ways to manage stress. The efficacy of these techniques may be enhanced when coupled with strategies to increase personal resilience amongst vulnerable groups (Weyrauch et al, 2001). Finally, while the odd ratios are small, this may be symptomatic of the examination of an "at risk" population.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, research indicates that experiencing a recent NLE (i.e., 2 days prior to suicide) was associated with less planning of that fatal act (Conner, Phillips, & Meldrum, 2007). Moreover , Weyrauch, Roy-Byrne, Katon, and Wilson (2001) demonstrated that certain past-year interpersonal NLEs, but not noninterpersonal NLEs, were related to less planning of a recent attempt. However, although previous results are suggestive of a NLE-planning interaction, little explanation has been provided for why NLEs may be particularly relevant for nonplanners.…”
Section: Moderation By Suicide Planningmentioning
confidence: 99%
“…An elevated risk for completed suicides was reported by a Danish study that used national registers (and thus overcame self-report problems): individuals in registered same-sex partnerships had about three-times greater risk for having committed suicide than those in opposite-sex marriages (Qin, Agerbo, & Mortensen, 2003). Moreover, a homosexual or bisexual orientation was a strong predictor for future suicides among psychiatric patients (Martin, Cloninger, Guze, & Clayton, 1985;Motto, Heilbron, & Juster, 1985) and a homosexual or bisexual self-identification was clearly overrepresented (25%) among failed suicides (Weyrauch, Roy-Byrne, Katon, & Wilson, 2001). Given these findings, it may be plausible to assume that the increased suicide risk of sexual minorities is not a result of weaknesses of research methods.…”
Section: Self-identificationmentioning
confidence: 99%